Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41598-021-94280-8
|View full text |Cite
|
Sign up to set email alerts
|

Dietary salt exacerbates intestinal fibrosis in chronic TNBS colitis via fibroblasts activation

Abstract: Intestinal fibrosis is a frequent complication in inflammatory bowel diseases (IBD). It is a challenge to identify environmental factors such as diet that may be driving this risk. Intestinal fibrosis result from accumulation of extracellular matrix (ECM) proteins secreted by myofibroblasts. Factors promoting intestinal fibrosis are unknown, but diet appears to be a critical component in its development. Consumption of salt above nutritional recommendations can exacerbate chronic inflammation. So far, high sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
(67 reference statements)
0
16
0
Order By: Relevance
“…56,59 In our study, there was no change in the expression of active calcium transport-related genes. As previously reported, this may be because the high-salt diet causes intestinal inflammation and fibrosis, 6062 which may disrupt normal intestinal function and then cause 1,25(OH) 2 D 3 is failed to regulate the genes related to calcium transport. In more recent studies, paracellular Ca 2+ absorption was shown to be associated with the claudin protein family.…”
Section: Discussionmentioning
confidence: 84%
“…56,59 In our study, there was no change in the expression of active calcium transport-related genes. As previously reported, this may be because the high-salt diet causes intestinal inflammation and fibrosis, 6062 which may disrupt normal intestinal function and then cause 1,25(OH) 2 D 3 is failed to regulate the genes related to calcium transport. In more recent studies, paracellular Ca 2+ absorption was shown to be associated with the claudin protein family.…”
Section: Discussionmentioning
confidence: 84%
“…Accordingly, a few studies using murine colitis models have observed that a high-salt diet exacerbates colitis, inducing an environment increasingly vulnerable to inflammatory insults [ 82 ]. Recently, we have characterised the effect of a high-salt diet on intestinal fibrogenesis using murine chronic colitis and cellular models of intestinal fibrosis [ 83 ]. Indeed, in our study, a high-salt diet increased mRNA transcripts encoding for pro-fibrotic markers, such as CTGF and collagen I, in chronic TNBS-induced colitis rats.…”
Section: Factors That Influence Macrophage Polarisation In Inflammati...mentioning
confidence: 99%
“… 25 MiR-155 was demonstrated to directly target HMG-box transcription factor 1 and then activate Wnt/β-catenin signaling pathway, leading to intestinal fibrosis [ Figure 2(b) ]. 26 Amamou et al 30 reported that a high-salt diet also contributed to the activation of colon fibroblasts and intestinal fibrosis. The authors observed a significantly increased expression of fibrosis markers (e.g.…”
Section: Search Strategymentioning
confidence: 99%